Gabapentin in the Management of Pain following Tonsillectomy: A Randomized Double‐Blind Placebo‐Controlled Trial. (25th July 2017) - Sanders, James G.; Cameron, Claire; Dawes, Patrick J. D.
Abstract : Objective: To determine if a single dose of oral gabapentin given prior to tonsillectomy decreases postoperative morbidity. Study Design: Prospective randomized double‐blind placebo‐controlled trial. Setting: Southern District Health Board University Hospitals, New Zealand, over a 10‐month period. Subjects and Methods: Seventy‐three adults undergoing tonsillectomy were randomized to receive either a single preoperative dose of oral gabapentin (600 mg) or placebo. A standard analgesic protocol was prescribed for 14 postoperative days. The primary outcome was a patient‐assigned visual analog scale pain score during rest and swallow; secondary outcomes were analgesic consumption, nausea, vomiting, and return to normal diet and activities. Complications and adverse effects were also recorded. Results: Thirty‐seven participants were allocated to the placebo group and 36 to the gabapentin group. After withdrawals, data were analyzed from 31 in the placebo group and 27 in the gabapentin group. Pain scores between groups were not significantly different within the first 6 hours. The gabapentin group recorded significantly higher pain scores between days 5 and 10 (maximal difference, day 8: 17.6 mm; effect size, –8.87; P =. 03; 95% CI, −16.883 to −0.865). There was no significant difference in swallow pain scores or early postoperative fentanyl consumption. Consumption of paracetamol ( P =. 01 at day 13 and P =. 004 at day 14) and codeine ( P <. 05 at days 3‐5, 7, 8, 10, 14) was higher in the gabapentin group. No significant difference between groups was found for the other outcomes. Conclusions: Preemptive gabapentin (600 mg) was associated with greater postoperative pain scores and analgesic consumption following adult tonsillectomy when compared with placebo.